DIAGNOSTIC AND THERAPEUTIC MODALITIES IN THE MANAGEMENT OF OPTIC DISC PIT MACULOPATHY- CASE REPORT AND LITERATURE REVIEW - Pandilov, Stefan; Sekerinov, Natasa Trpevska (Journal of Morphological Sciences, 2023)
Optic disc pit is an oval depression that is usually located in the temporal sector of the papilla nervi optici. It can be asymptomatic, but can also be the cause of maculopathy, optic disc pit-associated maculopathy (OPM). Its etiology is still not fully known, but modern imaging techniques in ophthalmology (OCT and OCT-A) have helped to better understand the pathophysiology of this entity. The purpose of this paper is to present a case with optic disc pit maculopathy, but also to give an overview of the pathogenesis, clinical aspects, imaging methods and therapeutic modalities in the management of patients with this pathology.   Keywords: optic disc pit, pars plana vitrectomy, carbonic anhydrase inhibitors, optic disc pit maculopathy.